Peripheral interleukin-6-associated microglial QUIN elevation in basolateral amygdala contributed to cognitive dysfunction in a mouse model of postoperative delirium - Mu, Jing-Lan; Liu, Xiao-Dong; Dong, Ye-Hong; Fang, Ying-Ying; Qiu, Shi-Da; Zhang, Fu; Liu, Ke-Xuan (Frontiers in Medicine, 2022)
Background Developing effective approaches for postoperative delirium has been hampered due to the lack of a pathophysiologically similar animal model to offer insights into the pathogenesis. The study, therefore, aimed to develop a delirium-like mouse model and explore the underlying mechanism. Methods The three cycles of 10-min clamp following 5-min reopening of the superior mesenteric artery (SMA) were performed in adult male C57BL/6 mice to induce a delirium-like phenotype. Composite Z score calculated based on the results of Open Field, Y Maze and Buried Food Tests was employed to assess the delirium phenotype in mice. Microglia activities were monitored by immunofluorescence staining and comprehensive morphological analysis. Systemic administration of minocycline (MINO), IL-6 antibody or IL-6 neutralizing antibody, was applied to manipulate microglia. The expressions of Indoleamine 2,3-dioxygenase-1 (IDO-1) and quinolinic acid (QUIN) were examined by RT-PCR and High-Performance Liquid Chromatography/Mass Spectrometry, respectively. Cytokines were measured using fluorescence activated cell sorting method. Results The repeated ischemia/reperfusion (I/R) surgery caused significant anxiety (P < 0.05) and cognition decline in working memory and orientation (P < 0.05) in mice at postoperative 24 h. The composite Z score, indicating an overall disturbance of brain function, fluctuated over 24 h after I/R surgery (P < 0.001). Immunofluorescent staining showed that the percentage of microglia in the basolateral amygdala (BLA) (P < 0.05) was reactivated after I/R surgery and was negatively correlated with dwell time at Y maze (R = −0.759, P = 0.035). Inhibiting microglia activities by MINO reduced QUIN productions (P < 0.01) that improved cognitive deficits (P < 0.05). The peripheral IL-6 might cause IL-6 elevation in the BLA. Systemic administration of IL-6 antibodies suppressed I/R-induced IL-6 elevations (P < 0.05), microglial reactivations (P < 0.05), IDO-1 expressions (P < 0.01), and neuroactive metabolite QUIN productions (P < 0.05) in the BLA, resulting in a recovery of cognitive deficits (P < 0.05). Injection of IL-6 exerted opposite effects. Conclusion The repeated intestinal I/R surgery-induced mouse model is a simple and reproducible one of postoperative delirium. Peripheral IL-6-associated microglial QUIN elevations in the BLA contributed to cognitive dysfunction in the model of postoperative delirium.